Effect of polymer concentration on the morphology of the PHPMAA-g-PLA graft copolymer nanoparticles produced by microfluidics nanoprecipitation - Petrova, Svetlana Lukáš; Pavlova, Ewa; Pokorný, Václav; Sincari, Vladimir (Nanoscale advances, 2024)
Successful generation of micelles, vesicles, and/or worms with controllable sizes was achieved through the self-assembly process of the poly[N-(2-hydroxypropyl)]methacrylamide-g-polylactide (PHPMAA-g-PLA) graft copolymer within a microfluidic channel. A product diagram was created to illustrate various morphologies associated with different polymer concentrations, all while maintaining a constant flow velocity ratio between water and the polymer solution.